KAJIAN PENGEMBANGAN PELABUHAN DALAM MENDUKUNG IBU KOTA BARU BERDASARKAN KONSEP SMART CITY, SMART MOBILITY - Malisan, Johny; Sujarwanto, Sujarwanto; Arief, Budi; Fadhil, Dimas Nu’man; Rahardjo, Sri (Jurnal Sistem Transportasi & Logistik, 2021)
The government has officially announced that the new capital city will be located in the province of East Kalimantan and will have a different infrastructure from the rest of Indonesia. This new region will apply digital technology that triggers the maritime industry to switch from traditional to digital processes as a consequence of development with the concept of smart city and smart mobility. This study aims to select and determine existing ports that meet the requirements to be developed to support development in the national capital region based on the concept of a smart city, smart mobility, as well as innovations that can be made to accelerate its development. In the conditions of the COVID-19 pandemic, the research was conducted online, using descriptive and qualitative methods. The results showed that the Semayang port and the Kaltim Kariangau Terminal (KKT) port were the selected ports, as well as other potential ports such as the Kampung Baru Tengah port and the Penajam Passer port. The two ports need to be developed towards a smart port that prioritizes efficiency and utilization of digital-based information system technology.